"Are You Clean?" Encouraging STI Communication in Casual Encounters through Narrative Messages in Romance Novels. Issue 3 (4th May 2021) - Rader, Kara; Hovick, Shelly R.; Bigsby, Elisabeth
ABSTRACT: Rates of sexually transmitted infections (STIs) are on the rise among young women, and a key factor in STI prevention is partner communication about STIs. Because entertainment narratives are shown to positively influence behavior change, the current study examined whether exposure to a romance novel excerpt wherein successful STI communication was modeled (versus one without) was associated with increased STI communication intentions. Guided by the Integrative Model for Behavioral Prediction, we also explored potential cognitive mechanisms of narrative exposure (i.e., self-efficacy, attitudes, normative beliefs) on behavioral intentions. Results of an experimental study with single, sexually-active college aged females (N = 166), showed exposure to a narrative including behavioral modeling was associated with increased perceived injunctive norms for STI communication. Self-efficacy and descriptive norms were also associated with STI communication intentions. Results suggest that when developing text-based STI communication narratives, it may be particularly important to build self-confidence and frame STI communication behavior as something others do.